2011
DOI: 10.1073/pnas.1112197108
|View full text |Cite
|
Sign up to set email alerts
|

Experimental free energy surfaces reveal the mechanisms of maintenance of protein solubility

Abstract: The identification of the factors that enable normally folded proteins to remain in their soluble and functional states is crucial for a comprehensive understanding of any biological system. We have determined a series of energy landscapes of the acylphosphatase from Drosophila melanogaster under a variety of conditions by combining NMR measurements with restrained molecular dynamics simulations. We thus analyzed the differences in the structures, dynamics, and energy surfaces of the protein in its soluble sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 43 publications
4
76
0
Order By: Relevance
“…In particular, we suggest that in specific cases large flexible loops in proteins may act to inhibit aggregation as a result of their high values of conformational entropy. It is well established that the aggregation propensity of proteins depends on the properties and population of all the conformational states within the ensemble, including the N* aggregation-prone species (14,15). The present results may provide a clear example of this concept by demonstrating that the flexibility of the ground state of EAS (the highly soluble state in bulk solution) is remarkably different from that of the aggregation-prone state (at the air-water interface).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In particular, we suggest that in specific cases large flexible loops in proteins may act to inhibit aggregation as a result of their high values of conformational entropy. It is well established that the aggregation propensity of proteins depends on the properties and population of all the conformational states within the ensemble, including the N* aggregation-prone species (14,15). The present results may provide a clear example of this concept by demonstrating that the flexibility of the ground state of EAS (the highly soluble state in bulk solution) is remarkably different from that of the aggregation-prone state (at the air-water interface).…”
Section: Discussionmentioning
confidence: 56%
“…The dynamic properties of proteins can play key roles in influencing their propensity for self-ssembly and aggregation (14) and have considerable significance in many aspects of their function (27)(28)(29)(30)(31). More generally, a range of factors discriminate between aggregation-prone and aggregation-resistant states of proteins, including charge effects, negative design elements and accessibility of aggregation-prone sequences (7,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative analysis of the structure of this domain with other Ig-fold domains clearly unveils that the Ig-domain of PrkC lacks the N-terminal strand. Although further studies are needed to define the role of this new type of incomplete Ig-fold domains, it has been suggested that the exposure of an anomalously large number of backbone -strand hydrogen-bond donors and acceptors may endow these domains with adhesive properties [86][87][88]. On analogy with the E. coli pilus subunit PapG, PrkC Ig-like domain may be involved in peptidoglycan binding [30,85].…”
Section: Structural Features Of Stpk Extra-cellular Regionmentioning
confidence: 99%
“…It is also becoming increasingly evident, however, that some normally folded proteins can aggregate from native-like states (N*) that are directly accessible from the native state (N) without the need for a transition across the major energy barrier for unfolding (reviewed in (7)). Formation of N* states may be promoted by mutations or subtle changes in solution conditions, for example, inducing the displacement of an edge b-strand and the subsequent exposure of aggregationprone regions of the protein (8)(9)(10)(11)(12)(13). As an alternative possibility, the release of a ligand may expose an aggregation-prone binding site (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%